Evaluation of the biotechnological potential of peptide Cupiennin 1a and analogs - Araújo, Rayssa Oliveira; Leite, Michel Lopes; Dutra, Thais Tavares Baraviera; Brito da Cunha, Nicolau; Rezende, Taia Maria Berto; Ramada, Marcelo Henrique Soller; Dias, Simoni Campos (Frontiers in Microbiology, 2022)
Antimicrobial peptides (AMPs) are components in the innate immune system of various organisms, and many AMPs can be found in poisons from animals such as spiders, scorpions, and snakes. The peptide Cupiennin-1a is present in the venom of the spider Cupiennius salei and belongs to a group of peptides called cupiennins. The peptide demonstrated high cytotoxic activity against mammalian cells; thus, aiming to solve this problem, seven analogues were designed (R1a, R1b, R2b, R3b, R6b, R8b and R10b) based on the primary structure of the peptide Cupiennin 1a, reducing its size and substituting some amino acid residues. The antimicrobial results showed that all Cupiennin 1a analogues displayed antimicrobial activity against the tested bacterial and fungal strains. Cytotoxicity tests demonstrated a decrease in the cytotoxic effect of the analogues when compared to the peptide Cupiennin-1a. The antitumor activity against breast adenocarcinoma strains was observed for all peptides, showing a better effect against MCF-7 and MDA MB-231 cell lines. The 8 peptides have insecticidal potential, and the original peptide and analogues R6b, R8b, and R10b showed better efficiency even at low concentrations. The rational design of the analogues led to new molecules displaying activities against different cell types and reduced cytotoxicity towards healthy mammalian cells when compared to the original peptide, demonstrating that this was an interesting approach for the development of molecules with biotechnological potential.